Presencia de orius insidiosus (say) (hemiptera: anthocoridae) en inflorescencias de mango ataulfo en el soconusco, Chiapas, México - Santiesteban-Hernández, Antonio; Virgen-Sánchez, Armando; Henaut, Yann; Cruz-López, Leopoldo (Instituto de Ecología, A.C., 2011)
The pirate bug Orius insidiosus (Say) was found for the first time in the inflorescences of mango cultivar Ataulfo in Soconusco, Chiapas, Mexico.